Impaired Expression and Function of Cancer-Related Enzymes by Anthocyans: An Update - Bei, Roberto; Palumbo, Camilla; Masuelli, Laura; Turriziani, Mario; Vanni Frajese, Giovanni; Li Volti, Giovanni; Malaguarnera, Michele; Galvano, Fabio (Current Enzyme Inhibition, 2012)
Anthocyans (ACNs), i.e. anthocyanins and anthocyanidins, belong to a widespread group of plant constituents, collectively known as flavonoids, which occur in the western diet at relatively high concentrations. ACNs display a variety of pharmacological properties which make them potential anti-inflammatory and anti-cancer agents. In addition to their ability to scavenge reactive oxygen species, ACNs can affect the functions of enzymes involved in DNA damage and in cancer-related signaling pathways. The antiproliferative, proapoptotic and antiangiogenic effects of ACNs rely on the inhibition of signaling by tyrosine kinase growth factor receptors (EGFR/ErBs, c-Met, VEGFRs, PDGFRs) as well as on the impairment of cAMP phosphodiesterase, proteasome chymotrypsin-like, ornithine decarboxylase and glyoxalase I activity. ACNs interfere also with cancer cell invasion by lowering the expression of the urokinase-type plasminogen activator and matrix metalloproteinases. Further, these compounds have been found to affect the transcriptional activity of NF-κB by inhibiting the IκB kinase complex and histone acetyltransferases, the inhibition of NF-κB being closely linked with the downregulation of COX-2 expression. Finally, ACNs are regarded as multi-target kinase inhibitors due to their ability to bind and inhibit a number of signaling kinases, such as Raf, MEK, MAPKK4, PI3K and Fyn. This review will provide an update on the effects of ACNs on the expression and function of enzymes involved in cancer development and progression, and will discuss the preventive/therapeutic potential of these compounds against human cancers.
Keywords: receptor tyrosine kinases